Analysis of Food Vlogger Content Creativity on Consumer Buying Interest with Viral Marketing as a Mediation Variable (Survey on Sukabumi Culinary Followers on Instagram) - Sintia Fitra Aziza; Kokom Komariah; Resa Nurmala (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Information and communication technology has deeply ingrained in people's lives. It's as if people now live "dependently" and feel confused when they're far from technology, better known as social media. This study aims to analyze the impact of food vlogger content creativity on consumer purchasing interest, with viral marketing as a mediating variable. The research method used is a quantitative research method with an associative descriptive approach. The objects of this study are content creativity, viral marketing, and consumer purchasing interest. The population in this study were Sukabumi Culinary followers on Instagram. The sampling technique used was a probability sampling technique of simple random sampling, resulting in a sample of 225 respondents. The data collection technique used in this study was a questionnaire distribution using Google Forms. The data analysis technique used was Structural Equation Modeling (SEM) using partial least squares (PLS). The results showed that content creativity has a significant influence on consumer purchasing interest of 3,953. In addition, it was found that viral marketing plays a significant mediating variable in the relationship between content creativity and consumer purchasing interest of 10,661.